Understanding the determinants of circadian health disparities and cardiovascular disease. (2nd January 2023) - Johnson, Dayna A.; Cheng, Philip; FarrHenderson, Maya; Knutson, Kristen
ABSTRACT: Emerging research suggests that sleep contributes to racial disparities in cardiovascular disease (CVD). Racial/ethnic minorities are disproportionately affected by poor cardiovascular outcomes including obesity, hypertension and diabetes. Although circadian rhythms affect sleep patterns, few studies have examined disparities in circadian health or the contribution of circadian disparities to CVD. In this paper, we provide an overview of the relation between circadian health and CVD in the context of health disparities. We discuss (1) the current knowledge on racial disparities in circadian health; (2) social and environmental determinants of circadian health disparities; (3) the cardiovascular consequences of circadian disparities; and (4) future opportunities to advance the field of circadian disparities. In brief, our findings demonstrated that among a small literature, racial minorities (mainly African American) were more likely to have a shorter circadian period, delayed phase shifts, and were more likely to be shift workers, which are associated with CVD risk factors. Given racial minorities are disproportionately affected by CVD and CVD risk factors, it is important to further understand circadian health as an intervention target and support more research among racial minorities to understand circadian health in these populations.